Exploring the Relationship Between Learning Goal Orientation and Knowledge-Sharing Among Information Communication Technology Consultants: The Role of Incentive Schemes - Song, Linpei; Ma, Zhuang; Huang, Jun (Frontiers in Psychology, 2022)
Knowledge sharing (KS) is critical for consulting companies to develop sustainable competitive advantages. While the importance of KS in the information communication technology (ICT) sector has been proved, the assumed linear relationships in KS mechanisms are confronted with KS dilemmas: consultants' intention to maximize personal gains from KS resulting in restrained KS efforts, for fear of losing value after sharing knowledge with colleagues (i.e., opening the kimono). Drawing on motivation theory and goal orientation perspective, this study examines the roles of learning goal orientation (LGO) and incentive schemes in KS among ICT consultants. The multiple regression analyses of 389 consultants' responses from 14 Chinese and 8 Korean ICT consulting companies demonstrated an inverted U-shape relationship between LGO and knowledge sharing; incentive schemes moderate this relationship. The findings shed light on the knowledge-sharing dilemma, with theoretical implications to research regarding goal-orientation, self-regulation, knowledge sharing, and managerial practices about the motivation and incentives of ICT consultants.